Cenozoic Stratigraphy of the East Java Forearc - A.M. Surya Nugraha; Robert Hall (Berita Sedimentologi, 2013)
The study area is located in the offshore SE Java and is situated at the southeast edge of the Eurasian plate, known as Sundaland. Sundaland is the continental core of SE Asia and was constructed by amalgamation of continental blocks during the Mesozoic. The East Java Forearc is a relatively unexplored area and the basement has long been considered to be Cretaceous arc and ophiolitic-accretionary complexes. But now there is increasing evidence for continental crust beneath the East Java Sea, and the southern part of East Java.This article presents the findings of an MSc study (Nugraha, 2010) and a geological history presented in an IPA paper (Nugraha and Hall, 2012). New seismic lines south of Java have imaged a deep stratified sequence which is restricted to East Java and is absent beneath the West Java forearc. Main datasets were provided by TGS, comprising three long-offset 2D-seismic datasets (SJR-9, SJR-10, and SJI-10). These data consist of thirty-seven 2D marine seismic lines across the Java forearc with a total of 8266 km survey length. Previously published seismic data (Kopp et al., 2006) were limited to shallow imaging 4-streamer seismic sections.